Genetic variation among hevea provenances - Paiva, João Rodrigues de; Gonçalves, Paulo de Souza; Gasparotto, Luadir (Pesquisa Agropecuaria Brasileira, 2014)
One-year old Hevea seedlings originated from 36 different provenances were evaluated for stem diameter, plant height and number of leaf flushes. Disease tolerance was evaluated when the plants were seventeen months old. The seeds were collected from native trees in 14 distinct areas covering six localities in Acre state, two in Mato Grosso state and six in Rondônia state, Brazil. The design used was a triple lattice 6 x 6 with 50 plants per plot, at a spacing, of 4 by 4 meters. The preliminary results from this study showed that the RO/CM/10, MT/C/04 and MT/C/06 provenances were the most vigorous. On the other hand, AC/S/08 and AC/S/11 showed the poorest vigour. The provenances originated from native trees located in the "varzea" (seasonal flooded area) showed the best behaviour in terms of vigor. In general, those provenances coming from Rondônia were more vigorous than those from Acre and Mato Grosso. In addition, provenances from the districts of Costa Marques (Rondônia), Ariel (Mato Grosso) and Tarauacá (Acre) contributed proportionally more to the estimated variation among the provenance in each state for the character of vigour. The pararneters used for evaluation of genetic variation of the population showed high variability useful for selection. All the provenances showed high susceptibility to Microcyclusulei while the incidence of Thanatephorus cucumeris and Colletotrichum gloeosporioides was less intense and more variable.